Komunikasi Politik dalam Lintasan Sejarah Politik Islam - Kartini Kartini; Anang Anas Azhar; Hasyim Syah (Jurnal Ilmiah Teknik Informatika dan Komunikasi, 2025)
This study discusses political communication as an important element in the political system, covering basic concepts, definitions from various perspectives, objectives, and its historical development. Political communication is understood as the process of conveying messages related to power, policy, and distribution of resources in society, which occurs between political actors, institutions, and the public. In addition to reviewing modern concepts, this study also traces the traces of political communication in Islamic history, especially during the time of the Prophet Muhammad SAW. This study shows that the Prophet Muhammad SAW applied the principles of political communication effectively in building a Muslim community, spreading Islamic teachings, managing conflicts, and establishing a state in Medina. Political communication in this context plays an important role in shaping public opinion, strengthening political participation, and delivering strategic information. These findings confirm that political communication has strong historical roots and high relevance in understanding political dynamics, both in classical and contemporary contexts.